Synthesis of (−)‐Morphine: Application of Sequential Claisen/Claisen Rearrangement of an Allylic Vicinal Diol. Issue 1 (23rd November 2012) - Ichiki, Masato; Tanimoto, Hiroki; Miwa, Shohei; Saito, Ryosuke; Sato, Takaaki; Chida, Noritaka
Abstract A detailed exploration of the synthesis of (−)‐morphine based on sequential [3, 3]‐sigmatropic rearrangements is described. The sequential Claisen/Claisen rearrangements of an allylic vicinal diol resulted in the stereoselective formation of the two contiguous carbon centers, including a sterically encumbered quaternary carbon, in a single operation. The two ethyl esters generated in this reaction were successfully differentiated during a subsequent Friedel–Crafts‐type cyclization. The (−)‐morphine double bond was introduced at a late stage in our first‐generation synthesis, but was formed at an earlier stage in the second‐generation synthesis, resulting in a more efficient route to the end product.